The Law, Economics and Politics of Retaliation in WTO Dispute Settlement. - Bown, Chad P. (Cambridge International Trade and Economic Law, 3., 2010)
A critical assessment of trade retaliation in the WTO by academics, diplomats and practitioners involved in such actions.